Hiperrealitas Perspektif Agama di Desa Sei Apung Jaya Kecamatan Tanjung Balai Kabupaten Asahan - Putri, Mulida (YASIN, 2023)
This study entitled Hyperreality of Religious Perspective in Sei Apung Jaya Village, Kec. Tanjung Balai Kab. Asahan explains how religion views hyperreality. The development and sophistication of technology today with various kinds of offers in online and real media, makes mothers, teenagers and even children tempted by this. Social status and friendship are seen from how sophisticated the Smartphone is and the style they consider cool and up to date. The K-Pop fashion style is no stranger to seeing teenagers today. The methodology used in this research is field research using a descriptive qualitative approach. Data was collected through interviews, observation and documentation. Data analysis was performed using descriptive analysis techniques. Based on the results of the study, it shows that the Sei Apung Jaya village community has a hyperreality attitude in shopping and a hyperreality in using social media. Hyperreality or exaggeration is forbidden in Islam. Many verses and hadiths warn that excess is dangerous and of course Allah SWT does not like excess.